Pathological complete response and prognostic predictive factors of neoadjuvant chemoimmunotherapy in early stage triple-negative breast cancer - Xuwei Chen; Xuwei Chen; Xuwei Chen; Hengming Ye; Daming Xu; Daming Xu; Siqi Chen; Siqi Chen; Siqi Chen; Wei Wu; Wei Wu; Wei Wu; et al. (Frontiers in Immunology)
BackgroundNeoadjuvant chemoimmunotherapy (nCIT) has shown promise in treating early-stage triple-negative breast cancer (eTNBC), but predictive biomarkers for pathological response and prognosis remain poorly defined.ObjectiveThis study aimed to explore pathological complete response and prognostic predictive factors in eTNBC patients treated with nCIT.Materials and methodsWe retrospectively analyzed 112 eTNBC patients who underwent surgery after nCIT at Sun Yat-sen University Cancer Center between June 2019 and June 2023. Pathological response was assessed using Miller-Payne grade. Clinicopathological features and hematologic markers were analyzed with univariate and multivariate logistic regression or Cox regression, as well as Kaplan-Meier survival curves. Objective response rate (ORR), pathological complete response (pCR), and disease-free survival (DFS) were evaluated. Nomograms predicting pCR and DFS were constructed based on significant risk factors and the systemic inflammatory response index (SIRI).ResultsHigher baseline lymphocyte counts (P=0.004) were independently associated with a higher pCR rate, while elevated monocyte counts (P=0.006), neutrophil-to-lymphocyte ratio (P=0.005), platelet-to-lymphocyte ratio (p = 0.005), SIRI (P=0.037), systemic immune-inflammation index (P=0.029), and preoperative SIRI (P=0.010) were associated with a lower pCR rate. Higher baseline SIRI (P= 0.009) was correlated with shorter DFS, while higher preoperative lymphocyte counts (P=0.019) predicted longer DFS. Nomograms incorporating SIRI showed high accuracy in predicting pCR and DFS.ConclusionHematologic inflammatory markers, particularly SIRI, are cost-effective and reliable predictors of prognosis and treatment efficacy in eTNBC patients undergoing nCIT, helping clinicians develop personalized treatment strategies.Clinical trial registrationhttps://www.medicalresearch.org.cn/, identifier MR-44-24-046099.